Comparative analysis of plagioclase in the Eyjafjöll ankaramites - Þrúður Helgadóttir 1984- (2016)
Eyjafjallajökull is the type locality for ankaramite in Iceland. This is an ultrabasic, porphyritic melanocratic basanite rock with abundant phenocrysts of clinopyroxene and olivine and plagioclase rich groundmass which also contains a considerable amount of oxides. Rock samples used in this study are from the ankaramitic outcrops in Hamragarðaheiði, Hvammsnúpur, Brattaskjól and Arnarhóll in Eyjafjöll. Hand specimens were briefly examined and plagioclase in thin sections were analysed by polarization microscope and SEM-EDS. Groundmass mineral assemblage according to CIPW norm calculation from average groundmass compositions showed Arnarhóll containing 60.5% plagioclase, 11% pyroxene, 24.9% olivine and 5.8% oxides, Hamragarðaheiði 54.5% plagioclase, 35.1% pyroxene, 3.3% olivine and 5.3% oxides. Brattaskjól contains 50.5% plagioclase, 33.3% pyroxene, 13.3% olivine and 4.1% oxides while Hvammsnúpur contains 57.5% plagioclase, 28.4% pyroxene, 8.6% olivine and 4.4% oxides. All samples were porphyritic. Arnarhóll and Hamragarðaheiði rock samples are rich in plagioclase phenocrysts, Hvammsnúpur samples have plagioclase phenocrysts in much less quantities and Brattaskjól sample had none. According to plagioclase chemical analysis in this study, anorthite content for plagioclase in the groundmass of the Brattaskjól samples is An73-77. Arnarhóll and Hvammsnúpur groundmass contain similar ranges, An58-72 and An41-70 respectively while the range is An51-60 in Hamragarðaheiði. Anorthite content range for plagioclase phenocrysts in Arnarhóll, Hamragarðaheiði and Hvammsnúpur samples is An79-90, An79-82 and An87-94 respectively. Olivine phenocryst chemical analysis was made for Brattaskjól and compared to olivine phenocryst data from Kristjánsson (2015) for Hamragarðaheiði and Hvammsnúpur. These three samples contained forsterite content range of Fo85-89, Fo67-78 and Fo70-70 respectively.